The attentional blink: A review of data and theory - Dux, Paul E.; Marois, René (Attention, perception & psychophysics, 2009)
Under conditions of rapid serial visual presentation, subjects display a reduced ability to report the second of two targets(Target2; T2) in a stream of distractors if it appearswithin200-500 msec of Target 1 (Tl). This effect. known as the attentional blink(AB),has been central in characterizing the limits of humans’ ability to consciously perceive stimuli distributed across time. Here, we review theoretical accounts of the AB and examine how they explain key findings in the literature. We conclude that the AB arises from attentional demands of Tl for selection, working memory encoding, episodic registration,and response selection, which prevents this high-level central resource from being applied to T2 at shortT1-T2 lags. Tl processing also transiently impairs the redeployment of these attentional resources to subsequent targets and the inhibition of distractors that appear in close temporal proximity to T2. Although these findings are consistent with a multifactorial account of the AB,they can also be largely explained by assuming that the activation of these multiple processes depends on a common capacity-limited attentional process for selecting behaviorally relevant events presented among temporally distributed distractors. Thus, at its core, the attentional blink may ultimately reveal the temporal limits of the deployment of selective attention.